Welfare at Slaughter of Broiler Chickens: A Review - Mota-Rojas, D.; Maldonado, M.J.; Becerril, M.H.; Flores, S.C.P.; Gonzalez-Lozano, M.; Alonso-Spilsbury, M.; Camacho-Morfin, D.; Ramirez, R.N.; Cardona, A.L.; Morfin-Loyden, L. (International Journal of Poultry Science, 2007)
Currently, poultry plants are sacrificing between 140 to 180 broilers per minute; sometimes animals are not sacrificed properly, which makes manual sacrifice necessary. In the present study a review is provided on the most relevant aspects regarding different methods used for chicken sacrifice, these methods are analyzed and a comparison with Mexican regulations is given regarding the humanitarian sacrifice of domestic birds for human consumption. We conclude that the main objective of broiler sacrifice should be the well-being of the animal, it must also be economic, practical and safe for workers. In Mexico, research must be developed to justify adequate use of sacrificial methods and its effect on the quality of poultry meat such as ostrich, turkey and quail.